Hospital management system on mainframe - Chai, Yee Toong (2012)
A hospital is a healthcare institute providing patient treatment through specialized staff and equipment,which are funded by public sector,health care organizations or health care charities.Healthcare in Malaysia is divided into public and private sectors.